Suicide risk in small-areas in England and Wales, 1991-1993 - Middleton, Nicos; Whitley, Elise; Frankel, Stephen J.; Dorling, Danny F L; Sterne, Jonathan Ac C C; Gunnell, David J. (My University, 2004)
Background There is growing evidence that areas characterised by high levels of social fragmentation have higher suicide rates. Previous ecological studies have focused on relatively large geographic areas and/or examined associations in all age groups combined. Methods Negative binominal regression was used to assess age- and sex-specific suicide rate ratios for a range of census-derived indicators of the social, health and economic characteristics of small areas (mean population aged ≥ 15: 4500) in England and Wales. Results Indicators of social fragmentation (e. g. proportion of people living alone or population mobility) were most consistently associated with suicide risk. For example, across quartiles of wards ranked according to increasing proportions of single-person households, age- and sexadjusted suicide rate ratios were: 1.00, 1.05 (1.00, 1.11), 1.14 (1.08, 1.19) and 1.42 (1.36, 1.49). Associations were strongest in 15 to 44 and 45 to 64 year-olds.Associations with social fragmentation persisted after controlling for the effect of other area characteristics. Conclusions Targeted mental health promotion and social policy initiatives to reduce area-health inequalities in suicide might usefully focus on areas with high levels of social fragmentation.
Keywords: Suicide; Small-area; Ecological study; Geographical inequalities; Socio-economic deprivation; Social fragmentation